Classic Antiphospholipid and Antiphosphatidylserine Antibody Profile in Suspected Antiphospholipid Antibody Syndrome Patient - Angga J Suryadi; Kanadi Sumapradja (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To compare the classic examination results of antiphospholipid (aPS) and antiphospatidylserine (aPL) antibody profile to establish the diagnosis from suspected antiphospholipid antibody syndrome (APS) patient in order to state the subsequent treatment strategies. Method: This descriptive cross-sectional study design was conducted at outpatient clinics of Dr. Cipto Mangunkusumo Hospital (RSCM) from January to December 2015. The laboratory test was held in Clinical Pathology Laboratory RSCM/Faculty of Medicine Universitas Indonesia (FKUI) and in corporation with Prodia laboratory. Result: All of normal patients did not have positive result in any laboratory examination (Lupus Anti-coagulant (LA), anticardiolipin (aCL), anti-?2 glycoprotein I (anti-?2GPI), and aPS). In patient suspected APS, 11 (37.1%) patients had positive aCL, 7 (25.9%) patients had positive anti-?2GPI, and 11 (37.1%) patients had positive aPS. The most positive cross laboratory examination was between aCL and aPS (25.9%). In this study, we found the most positive test result was aCL and aPS (62.9%). From this study, suspected APS patient who had negative result in classic laboratory examination, but showing the positive result in aPS was in 5 (18.5%) patients. Conclusion: All normal pregnant patients do not have any positive classic examination and aPS. Meanwhile, in patients with suspected APS, less than 20% patients show positive result of aPS with negative result in classic laboratory examination. Keywords: antiphospatidylserine, antiphospolipid syndrome